2021
DOI: 10.1149/1945-7111/abdc63
|View full text |Cite
|
Sign up to set email alerts
|

High Performance NiOx Extended-Gate Field-Effect Transistor Biosensor for Detection of Uric Acid

Abstract: In this paper, we developed a high performance NiOx extended-gate field-effect transistor (EGFET) biosensor for detection of uric acid. The structural and sensing properties of the NiOx sensing film deposited on a n+-type Si substrate was examined for an EGFET pH sensor. X-ray diffraction, atomic force microscope and X-ray photoelectron spectroscopy were used to analyze the film features of the NiOx sensing film. The NiOx sensing film based on EGFET exhibited a high pH sensitivity of 58.53 mV pH−1, a small hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Among these sensing architectures of EGFET, the present study's EGFET with the on-chip sensing window showed better sensitivity. In Pan's study [37], they fabricated an EGFET for UA detection using the off-chip sensing window with the uricase. Its disadvantage was that it can not achieve the miniaturized one-piece sensor.…”
Section: B Sensing Characteristics For Uric Acid Detectionmentioning
confidence: 99%
“…Among these sensing architectures of EGFET, the present study's EGFET with the on-chip sensing window showed better sensitivity. In Pan's study [37], they fabricated an EGFET for UA detection using the off-chip sensing window with the uricase. Its disadvantage was that it can not achieve the miniaturized one-piece sensor.…”
Section: B Sensing Characteristics For Uric Acid Detectionmentioning
confidence: 99%
“…Schistosoma mansoni 88,91,104,105,106,107 Sustentabilidade 39,56,59,60,62,121,124,129,130,132,133 T Tecido adiposo 27,29,30,36,37 Transistor de efeito de campo 1, 2, 4, 176…”
mentioning
confidence: 99%
“…Diante do exposto, o EGFET formado por dispositivo EIS, composto de óxido de alumínio e eletrodo de referência contendo membrana seletiva [217], [220], [221], mostrou-se muito promissor para a aplicação inédita que propôs o trabalho de pesquisa, que foi medir a concentração de fosfato no DTF em tempo real, e com a contribuição de quantificar a massa de fósforo que é removida do paciente renal crônico nas sessões de hemodiálise. Trouxe também uma contribuição significativa no que diz respeito ao controle do nível de concentração de fósforo em pacientes renais crônicos, pois de acordo com trabalhos relacionados na literatura [32], [35], [222], [223], mostram a relevância do controle do nível de concentração de fósforo nos pacientes renais crônicos.…”
Section: Medidas Da Concentração De Fosfato No Dtfunclassified